Prevalence of awareness, attitude, and practice towards tobacco use among general public in Kuantan - Al-Shami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Fata Nahas, Abdul Rahman; Elkalmi, Ramadan Mohamed Mahmod; Elsayed, Tarek Mohamed Ali; Akkawi, Muhammad Eid (2019)
Introduction: Several studies had been conducted to assess the awareness, attitude, and practice of a specific population towards cigarette smoking. However, other tobacco products are mostly neglected. In Malaysia, many tobacco products such as cigarettes, hand-rolled tobacco, shisha, cigar, pipe, and chewy tobacco are easily accessible. Yet, there are no established studies of tobacco use specifically among the general public in Kuantan. Objective: This study aimed to estimate the prevalence of tobacco use among the Kuantan general public and to assess the awareness, attitude and practice towards tobacco use. Method: This is a cross-sectional study. A pre-tested, structured, self-administered questionnaire was administered to a convenience sample (N = 202) in Kuantan from October to December 2018. The questionnaire was validated by experts and a pilot study was conducted to establish its reliability. Data were analyzed by SPSS using descriptive as well as inferential analysis. Results: The prevalence among the respondents was 43.6% (n = 88), in which 98.2% were males. Most of the respondents reported high awareness (91.1%) about tobacco use with the highest scores being achieved by males and those between 38 and 47 years old (96.0%). The majority of respondents demonstrated a positive attitude (97.02%) towards tobacco use, particularly among females and those between 38 and 47 years old (100%). In terms of practice, almost 50.5% reported poor practice, especially females and those who are between 18 and 27 years old. Conclusion: The prevalence of tobacco use among the general public of Kuantan is considered high. Most of the people in Kuantan have good awareness and attitude, however, their practice towards tobacco use was poor.